Chemotherapy and drug resistance in luminous bacteria from penaeid shrimp hatchery - Abraham, T Jawahar; Palaniappan, R (Indian Journal of Fisheries, 2011)
In-vitro activities of chloramphenicol, ciprofloxacin, nalidixic acid and oxytetracycline against antibiotic-sensitive luminous Vibrio harveyi, V.orientalis and V.splendidus1 from penaeid shrimp hatchery were evaluated. The antibiotic resistance rates for V.harveyi, V.orientalis and V.splendidus to chloramphenicol (1.92x10-10-9.38x10-8) and ciprofloxacin (1.92x10-10-2.45x10-9) were very low at 5 and 10 times of their respective minimal inhibitory concentration (MIC) than at 2 times the MIC. The resistance rates for luminous bacteria to nalidixic acid (4.02x10-9-1.45x10-2) and oxytetracycline (1.92x10-10-3.95x10-2) were found to be higher than chloramphenicol and ciprofloxacin. Although ciprofloxacin was effective in terms of MIC and induction of low level of resistant isolates, chloramphenicol was more active in its ability to control antibiotic-sensitive luminous bacteria.